The interconnections between services and goods trade at the firm-level - Andrea Ariu; Holger Breinlich; Gregory Corcos; Giordano Mion (National Bank of Belgium, 2017)
In this paper we study how international trade in goods and services interact at the firm level. Using a rich dataset on Belgian firms during the period 1995-2005, we show that: i) firms are much more likely to source services and goods inputs from the same origin country rather than from different ones; ii) increases in barriers to imports of goods reduce firm-level imports of services from the same market, and conversely. We build upon a discrete-choice model of goods and services input sourcing that can reproduce these facts to design our econometric strategy. The results suggest that a liberalization of service trade has direct and sizable effects on goods trade and vice-versa. Moreover, sourcing goods and services from the same origin brings substantial complementarities to both.
Keywords: F10; F13; F14; L60; L80; 330; Trade in Services; Trade in Goods; Complementarity; Firm-level Analysis; Discrete Choice Models